Epidemiology of cardiovascular malformations among newborns in Monchegorsk (north-west Russia): a register-based study - Vitaly A. Postoev; Ljudmila V. Talykova; Arild Vaktskjold (SAGE Publishing, 2014)
Background. Cardiovascular malformations (CVM) are one of the most prevalent groups of birth defects. Knowledge about the prevalence, distribution and survival in Russia has been limited. The aim of our study was to assess the perinatal prevalence, structure and risk factors for CVM among newborns in Monchegorsk (Murmansk Oblast, Russia) and the mortality among the affected newborns in the period 1973-2008. Design and methods. A register-based study on data from the Kola and Murmansk County Birth Registers. The study included 28,511 births. Results. The registered perinatal prevalence was 3.0 per 1000 newborns, with septal defects as the most prevalent. CVM was twenty times more prevalent among stillborn than live born, and one-third of the live born with a CVM died during the first week of life. The perinatal mortality rate with CVM was 442 per 1000 newborns. This indicator decreased over time. The mothers of newborns with a CVM were ten times more likely to have stillbirth in their anamnesis. The adjusted odds ratio between maternal smoking during pregnancy and CVM was 4.09 [95% confidence interval: 1.75-9.53]. Conclusions. The diagnosed perinatal prevalence was relatively low. A previous stillbirth by the mother was highly associated with being born with a CVM. An adjusted elevated risk was also observed among smoking mothers. Perinatal survival increased over time, but varied to a large extent between the different types of CVM.